Information technology and managed care. - Austin CJ; Sobczak PM (Hospital Topics)
Information processing in the managed care marketplace is becoming increasingly complicated and expensive. Managed care organizations are finding that the ability to process information effectively and efficiently is the only way to maintain a competitive edge. This article provides an overview of information needs and system requirements from the perspective of healthcare providers. It offers information about computer software, electronic data interchange and databases, as well as brief case reports on some of their uses.